Infertility and the Margins of Society: Medieval Churchmen think about Reproductive Disorders - Rider, Catherine (Studies in church history, 2025)
The history of infertility is a rapidly growing field but the relationship between infertility and religion remains under-studied. This article investigates the ways in which religious writers in the European Middle Ages thought about infertility, focusing (in keeping with the theme of "margins and peripheries") on how far these sources presented reproductive disorders as leading people to be marginalized or stigmatized. It examines several key sources discussed by earlier scholars before moving on to a detailed analysis of late medieval English retellings of the story of the birth of the Virgin Mary, who was born to her parents in old age. The article argues that there is some evidence that infertility could be viewed as a source of stigma and infertile people as marginalized. However, the narratives of the birth of the Virgin offered a more inclusive view, and were modified by different authors to reflect different experiences of infertility.